2020
DOI: 10.3847/1538-4357/aba633
|View full text |Cite
|
Sign up to set email alerts
|

Spitzer Follow-up of Extremely Cold Brown Dwarfs Discovered by the Backyard Worlds: Planet 9 Citizen Science Project

Abstract: We present Spitzer follow-up imaging of 95 candidate extremely cold brown dwarfs discovered by the Backyard Worlds: Planet 9 citizen science project, which uses visually perceived motion in multiepoch Wide-field Infrared Survey Explorer (WISE) images to identify previously unrecognized substellar neighbors to the Sun. We measure Spitzer [3.6]-[4.5] color to phototype our brown dwarf candidates, with an emphasis on pinpointing the coldest and closest Y dwarfs within our sample. The combination of WISE and Spitz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 89 publications
1
32
0
Order By: Relevance
“…New members of the 20 pc census have been announced not only by brown dwarf researchers specifically looking for examples (e.g., Kendall et al 2004) but also by researchers in unassociated fields who have serendipitously found others (e.g., Hall 2002;Thorstensen & Kirkpatrick 2003). New additions to the sample have been published as single-object papers (e.g., Ruiz et al 1997;Folkes et al 2007); as part of large photometric (e.g., Delfosse et al 1997;Lucas et al 2010), spectroscopic (e.g., Schmidt et al 2010), proper motion (e.g., Smith et al 2014;Meisner et al 2020aMeisner et al , 2020b, or parallax surveys (e.g., from Gaia: Reylé 2018; Scholz 2020); or as the result of dedicated searches for companions around higher mass stars (e.g., Freed et al 2003;Thalmann et al 2009) or around other brown dwarfs (e.g., Volk et al 2003;Gelino et al 2011). Construction of the census of the closest L, T, and Y dwarfs has been the effort of many dozens of lead authors presenting results in hundreds of publications.…”
Section: Building the Target Listmentioning
confidence: 99%
See 4 more Smart Citations
“…New members of the 20 pc census have been announced not only by brown dwarf researchers specifically looking for examples (e.g., Kendall et al 2004) but also by researchers in unassociated fields who have serendipitously found others (e.g., Hall 2002;Thorstensen & Kirkpatrick 2003). New additions to the sample have been published as single-object papers (e.g., Ruiz et al 1997;Folkes et al 2007); as part of large photometric (e.g., Delfosse et al 1997;Lucas et al 2010), spectroscopic (e.g., Schmidt et al 2010), proper motion (e.g., Smith et al 2014;Meisner et al 2020aMeisner et al , 2020b, or parallax surveys (e.g., from Gaia: Reylé 2018; Scholz 2020); or as the result of dedicated searches for companions around higher mass stars (e.g., Freed et al 2003;Thalmann et al 2009) or around other brown dwarfs (e.g., Volk et al 2003;Gelino et al 2011). Construction of the census of the closest L, T, and Y dwarfs has been the effort of many dozens of lead authors presenting results in hundreds of publications.…”
Section: Building the Target Listmentioning
confidence: 99%
“…Both the Backyard Worlds (Kuchner et al 2017) and CatWISE (Eisenhardt et al 2020) teams were continuing to identify new candidate late-T and Y dwarfs from WISE data as Spitzer hurtled toward its assigned decommissioning date in 2020 late-January. As chronicled in Meisner et al (2020aMeisner et al ( , 2020b, candidates lacking extant Spitzer photometry were added to Spitzer photometric programs 14034 (Meisner, PI), 14076 (Faherty, PI), and 14299 (Faherty, PI). As these new IRAC data became available, we used the new Spitzer photometry to predict a distance to each candidate using the M ch2 versus ch1−ch2 color 41 relation of Kirkpatrick et al (2019a).…”
Section: Building a List Of Probable 20 Pc L T And Y Dwarfsmentioning
confidence: 99%
See 3 more Smart Citations